Feasibility Study on Establishment of Fruity Poppers in Sta. Monica, Novaliches Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This research focused on establishing a business named Fruity Poppers in Sta. Monica,Novaliches,Quezon City. The business will offer a unique taste of food. It will use fresh ingredients and cook a mixture of different flavors. This paper addresses the feasibility and viability of the business in terms of marketability, technical aspect, management, and financial aspect. The proposed business will be patronized because the proponents are confident of its products. In addition to gaining profit, which is the main objective of business owners, providing quality that will satisfy the customer and employee was the objective of this study. The proponents were confident that the establishment of business will be realized and succeed. The key research tools were questionnaires, ocular visits, and observation of the market trends. The participants were selected using stratified sampling techniques. The result was analyzed manually because there were only 100 respondents. The proponents observed the viability and accessibility of the location place of the business where it will be established. The conceptualization initially commenced during brainstorming and focus group discussion. According to the respondents, the business location of Fruity Poppers is very accessible to prospective clients. A total of 67% of the respondents were male, while only 33% of the respondents were female. The average age of the respondent was between 18 and50 years old. Based on the results of the survey,75%of the respondents wanted to try the new mango flavor. Generally, 98% of the respondents liked the popcorn. This chapter outlined and justified the feasibility and viability of the business in the market. The interpretation by the researchers provided the significance of this research paper along with the recommendation on how the people within the company manage the business. This business is a general partnership type wherein the partners will share P200,000each, with the initial capital of P1,000,000. The allocation of the budget should ensure that there would be control over its related costs. The researchers predicted that there would be a 2% increase in expenses annually, while there will be a 10% increase in the cost of sales. The revenue is expected to have increased by 10%. Withthecompetencies and proper management of the business, the proposed business will be realized and become successful.
Keywords: establishment, feasibility study fruity poppers, marketability, ocular visit, proponents, sampling